PERAN KOMITE MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH DI KUTAI BARAT - Ikran Ikran; Zurqoni Zurqoni; Ity Rukiah (STKIP PGRI Situbondo, 2024)
The purpose of this study 1). To dive deeper into the role of the madrasah committee in efforts to improve the quality of education at MTs Negeri Kutai Barat and MAN Kutai Barat. 2). To dive deeper into the supporting and inhibiting factors of the role of the madrasah committee in efforts to improve the quality of education at MTs Negeri Kutai Barat and MAN Kutai Barat. This study used a qualitative approach with a phenomenological type, using interview data collection, observation and documentation, data analysis using the Miles, Huberman and Saldana analysis model techniques. The results of the study found that there were similarities and differences in the involvement of madrasah committees at MTs Negeri Kutai Barat and MAN Kutai Barat in terms of planning work programs. The similarities are; (1) at the beginning of every year to prepare a work program, (2) Planning is carried out for one year, (3) involving the head of the madrasa, teachers, education staff, committees, student guardians, and other related parties. Then the difference is that the Head of MTs Negeri Kutai Barat involves the Madrasah Committee in preparing the madrasah budget while the MAN Kutai Barat committee is not involved. The MTs Negeri Kutai Barat Committee is actively involved in repairing facilities and infrastructure such as repairing the paint of the madrasa building, making parking areas, etc. which are arranged in every work program planning meeting and funding is taken from the student's guardian routine fees of Rp. 30,000 for the payment of teachers' fees and others, while the MAN Kutai Barat committee is involved in improving facilities and infrastructure only conditionally, not routinely and is planned. The evaluation at the end of each year carried out by the two Madrasah Committees is a form of their responsibility for the programs that have been planned and implemented so that future improvements can be made and can contribute to improving the quality of education in each madrasah. Abstrak Tujuan penelitian ini 1). Untuk menyelami lebih dalam bagaimana peran komite madrasah dalam upaya meningkatkan mutu pendidikan di MTs Negeri Kutai Barat dan MAN Kutai Barat. 2). Untuk menyelami lebih dalam apa saja faktor pendukung dan penghambat dari peran komite madrasah dalam upaya meningkatkan mutu pendidikan di MTs Negeri Kutai Barat dan MAN Kutai Barat. Penelitian ini menggunakan pendekatan kualitatif dengan jenis fenomenologi, menggunakan pengumpulan data wawancara, observasi dan dokumentasi, analisis data menggunakan Teknik model analisis Miles, Huberman dan Saldana. Hasil penelitian menemukan ada persamaan dan perbedaan keterlibatan komite madrasah di MTs Negeri Kutai Barat dan MAN Kutai Barat dalam hal perencanaan program kerja. Persamaannya adalah; (1) setiap awal tahun melakukan penyusunan program kerja, (2) Perencanaan dilakukan selama satu tahun, (3) melibatkan kepala madrasah, guru, tenaga kependidikan, komite, wali siswa, dan pihak-pihak terkait. Kemudian perbedaannya adalah Kepala MTs Negeri Kutai Barat melibatkan Komite Madrasah dalam penyusunan anggaran belanja madrasah sedangkan komite MAN Kutai Barat tidak dilibatkan. Komite MTs Negeri Kutai Barat terlibat aktif dalam perbaikan sarana dan prasarana seperti perbaikan cat gedung madrasah, pembuatan area parkir, dan lain-lain yang disusun dalam setiap rapat perencanaan program kerja serta pendanaan yang diambil dari iuran rutin wali siswa sebesar Rp. 30.000 untuk pembayaran honor guru dan lain-lain, sedangkan komite MAN Kutai Barat keterlibatannya dalam perbaikan sarana dan prasarana hanya kondional saja, tidak rutin dan disusun dalam perencanaan. Evaluasi setiap akhir tahun yang dilakukan oleh kedua Komite Madrasah adalah bentuk tanggung jawab mereka terhadap program yang sudah direncanakan dan dilaksanakan agar bisa dilakukan perbaikan kedepannya dan dapat memberikan sumbangsih peningkatan mutu pendidikan di masing-masing madrasah